B2B Sales Meeting Course as an Effort to Build Student Sales Skill - Hidayat, Hajan; Zuliarni, Sri; Sari, Desi Ratna; Hati, Shinta Wahyu; Naysila, Assyfa; Putri, Aprilia Prastiana (Politeknik Negeri Batam, 2023)
Appropriate and effective learning methods are needed that are truly able to develop sales skills, especially Business to Business (B2B) sales. This study aims to empirically test how effective the Project Based Learning B2B Sales Meeting organized by the Applied Business Administration Study Program is in improving student sales skills. The method used to answer research problems is Quasi Experiment method. The results of hypothesis testing using the t-test showed that there were significant differences in the pretest and posttest scores of the research subject's sales skills and the posttest scores showed a higher value than the pretest scores. Thus PBL B2B Sales Meeting is effective in improving sales skills of research subjects. With the proven effectiveness of the PBL method, it is recommended that this method be applied in other courses.